GE_GERICHTE P/12256/2024 vom 13. Mai 2025 - GE Cour de justice (2025)
VOL(DROIT PÉNAL);INFRACTION PAR MÉTIER;AFFILIATION À UNE BANDE;BRIGANDAGE;TENTATIVE(DROIT PÉNAL);IN DUBIO PRO REO;REPENTIR SINCÈRE;CONCOURS D'INFRACTIONS;RÈGLEMENT (CE) 1987/2006;EXPULSION(DROIT PÉNAL);TORT MORAL | CP.139; CP.140.al3; CP.22; CP.48.letd; CP.49.al1; CO.47